Institutionalization of the Sociology of Consumption in Russia - Olga Gurova (Экономическая социология, 2014)
This article explores the process by which a subfield of sociology, the sociology of consumption, became institutionalized in Russia. By “institutionalization” is meant the process of its establishment as an autonomous field of scientific knowledge, university-level discipline and academic community of scholars. Drawing on data from document analysis and expert interviews, the article reviews the evolution of the sociology of consumption— its topics, methodologies and approaches — in Soviet and post-Soviet Russia. We look at its emergence and functioning as a subject in university curricula and the formation of a community of scholars self-identifying as belonging to this field. The main observations are the following: while the institutionalization of the sociology of consumption accelerated in the 1990s, its origins can be traced to the beginning of the 20th century. The subfield continues to be in the process of formation in Russia. Currently, two major approaches can be discerned: the socio-economic and socio-cultural approaches. Since the 1990’s, Sociology of Consumption was included in university curricula as an elective course for students preparing themselves for a professional career in sociology. On one hand, this provoked a certain standardization. At the same time, scholars in Russia remain free to manipulate the content of a particular course. In terms of community, the experts we interviewed noted the lack of a “strong promoter” or “charismatic leader” but emphasized the existence of “growing points,” namely, places across the country where scholars at various universities play a particularly key role in developing the subfield and contributing to its further institutionalization.